2019
DOI: 10.1016/j.stemcr.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Gene Tagging of Transcriptionally Silent Genes in hiPSCs

Abstract: Summary We describe a multistep method for endogenous tagging of transcriptionally silent genes in human induced pluripotent stem cells (hiPSCs). A monomeric EGFP (mEGFP) fusion tag and a constitutively expressed mCherry fluorescence selection cassette were delivered in tandem via homology-directed repair to five genes not expressed in hiPSCs but important for cardiomyocyte sarcomere function: TTN , MYL7 , MYL2 , TNNI1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…This offered an opportunity to test the proposition that RNA abundance levels correlate with cell organization (Battich et al, 2015;Gut et al, 2018;Popovic et al, 2018). We used an hiPSC line expressing mEGFP-tagged alpha-actinin-2 (ACTN2-mEGFP; Roberts et al, 2019), which localizes to the z-disk of the sarcomere, to quantify and stage sarcomere organization (Luther et al, 2011). The differentiated cardiomyocyte populations were replated for high resolution imaging and revealed a broad range of sarcomere organization with a general increase in myofibril organization over time ( Figure 3A, B).…”
Section: Cardiomyocytes Show Discernable Stages In Myofibrillar Organmentioning
confidence: 99%
“…This offered an opportunity to test the proposition that RNA abundance levels correlate with cell organization (Battich et al, 2015;Gut et al, 2018;Popovic et al, 2018). We used an hiPSC line expressing mEGFP-tagged alpha-actinin-2 (ACTN2-mEGFP; Roberts et al, 2019), which localizes to the z-disk of the sarcomere, to quantify and stage sarcomere organization (Luther et al, 2011). The differentiated cardiomyocyte populations were replated for high resolution imaging and revealed a broad range of sarcomere organization with a general increase in myofibril organization over time ( Figure 3A, B).…”
Section: Cardiomyocytes Show Discernable Stages In Myofibrillar Organmentioning
confidence: 99%
“…Generation of tagged-parvalbumin neurons by a CRISPR/Cas9 approach as a tool to follow PVALB neuron cell fate The CRISPR/Cas9 genome-editing technology (reviewed in [53]) has been broadly used to modify iPSC and recently, many studies successfully demonstrated the generation of human iPSC lines expressing a fluorescent protein that faithfully recapitulates the endogenous expression of a given protein [54,55]. Through a CRISPR/Cas9 approach, one could insert a reporter cassette (i.e., eGFP, tdTomato), whose expression is driven by the endogenous PVALB promoter, allowing to follow the fate of these neurons once PV expression starts.…”
Section: Asd Ipsc and Parvalbumin Interneuronsmentioning
confidence: 99%
“…Incomplete characterization of cell lines and insufficient reporting of details for creating and validating cell lines is common and may be an impediment to their adoption by others. While cell line characterization is quite extensive in some reports [14] , [17] , [26] , [96] too few are sufficiently documented. This failure leads to a lack of confidence in the biological significance of the data generated using these cell lines.…”
Section: Appropriate Engineering and Characterization Of Reporter Celmentioning
confidence: 99%
“…This failure leads to a lack of confidence in the biological significance of the data generated using these cell lines. Exemplars of thorough cell line validation and characterization include the Allen Institute for Cell Science (AICS) [96] and the European Molecular Biology Laboratory (EMBL) [87] . Both groups focus on the complete description of the reporter construction, the use of multiple methodologies to interrogate the details of the genomic editing accuracy and thorough evaluation of the functional properties of the reporter that relate to its ability to act as a biologically relevant expression surrogate for the GOI.…”
Section: Appropriate Engineering and Characterization Of Reporter Celmentioning
confidence: 99%